Experimental and Numerical Analysis of Springback Behavior of Aluminum Alloys - Slota, J.; Šiser, M.; Dvorák, M. (Проблемы прочности, 2017)
Presented work deals with springback behavior of two different aluminum alloys, one falling into 5th series (AW-5754 H22) with a thickness of 0.8 mm and other from 6th series (AW-6082 T6) with 1.0 mm thickness. These materials are used for their various applications and hardening process. The springback behavior was investigated by U-bending test. Bending tool was graduated jig with rollers and experiment was performed on R11 and R17 radii. The first series of specimens were oriented in a parallel direction and the other in a direction perpendicular to the rolling direction. Experimental results were measured with MATLAB measuring method and compared with finite element calculation carried out in PAM-STAMP. Influence of different yield functions was also examined.